2014
DOI: 10.1111/epi.12721
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral interictal spikes are related to tapetum damage in left temporal lobe epilepsy

Abstract: Summary Objective In temporal lobe epilepsy (TLE) the epileptogenic focus is focal and unilateral in the majority of patients. A key characteristic of focal TLE is the presence of sub-clinical epileptiform activity in both the ictal and contralateral "healthy" hemisphere. Such interictal activity is clinically important as it may reflect the spread of pathology, potentially leading to secondary epileptogenesis. The role played by white matter pathways in this process are unknown. Methods We compared three i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…[29] Specific white matter changes could be the structural basis for pathology spread as described in a recent diffusion tensor imaging study that found callosal fibers of the tapetum significantly more damaged in those with bilateral IED. [36] The lack of statistically significant differences in terms of seizure outcome after surgery between the three groups may be attributable to the low statistical power, as only 31 people underwent surgery. The small number of people proceeding to surgery eventually might be due to a selection bias in our cohort, as those undergoing repeated VT may represent a subgroup with difficult-to-assess epilepsies leading to more hesitant recommendations for surgery and lower estimated odds for postoperative seizure freedom.…”
Section: Discussionmentioning
confidence: 99%
“…[29] Specific white matter changes could be the structural basis for pathology spread as described in a recent diffusion tensor imaging study that found callosal fibers of the tapetum significantly more damaged in those with bilateral IED. [36] The lack of statistically significant differences in terms of seizure outcome after surgery between the three groups may be attributable to the low statistical power, as only 31 people underwent surgery. The small number of people proceeding to surgery eventually might be due to a selection bias in our cohort, as those undergoing repeated VT may represent a subgroup with difficult-to-assess epilepsies leading to more hesitant recommendations for surgery and lower estimated odds for postoperative seizure freedom.…”
Section: Discussionmentioning
confidence: 99%
“…Neither patient-reported seizure frequency nor disease duration showed a significant correlation at these tracts in our analysis, although a correlation with epilepsy duration has been found at the corpus callosum by some diffusion studies. 39,42 Furthermore, greater change at the corpus callosum has been found with refractory versus benign epilepsy, 43 in association with bilateral temporal interictal epileptiform discharges, 44 as well as in an experimental rat model of focal epilepsy where no antiepileptic medications were used. 45 Thus, our interpretation is that atrophy in these tracts is likely to be a consequence of factors that have a bilateral and symmetrical impact, with generalized seizures, antiepileptic medications, and other global factors such as psychological and socioeconomic status all being possible causes.…”
Section: Common Bilateral Abnormalities In Hs-tle and Mri-neg Tle: A mentioning
confidence: 99%
“…There is growing body of evidence that brain abnormalities in focal epilepsies such temporal lobe epilepsy (TLE) are not limited to the epileptogenic region, but extend into widespread areas of the whole brain. These extra-temporal abnormalities have emerged from gray matter (GM)[ 1 ], white matter[ 2 , 3 ], metabolic[ 4 , 5 ], and, more recently, resting-state fMRI investigations (see review by [ 6 ]). In terms of structural abnormalities, voxel-based morphometry (VBM) studies in TLE have been effective in demonstrating reduced GM volume in multiple brain regions such as the mesial temporal lobe, thalami, insula, or sensory motor cortex[ 1 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%